Implementation of mHealth to support cancer diagnosis in Sub-Saharan Africa: A systematic review - Kirsten D. Arendse; Grace A. Baby; Teffanie T.M. Maramba; Jennifer Moodley; Fiona M. Walter; Suzanne E. Scott (African Journal of Primary Health Care & Family Medicine)
Background: A reduction in communicable diseases in sub-Saharan Africa (SSA) over recent decades has led to an increased life expectancy and non-communicable diseases such as cancer. However, cancer services in SSA remain inadequate. With increasing mobile use, mobile health (mHealth) has the potential to expand healthcare access.